RARE COMPLICAION AFTER NEPHRON-SPARING SURGERY IN COMPLEX PT3A KIDNEY CANCER PATIENTS: A CASE REPORT - Pavel Yakovlev; Nikolaienko Sofiia; Nataliia Zokhniuk; Sergii Pasiechnikov (Bogomolets National Medical University, 2018)
Absract. Benefit of partial nephrectomy compered to radical nephrectomy have shown by numerous studies as this preserves most of the functioning kidney, thus preventing onset of chronic kidney failure and potential cardio-vascular mortality. In the same time, partial nephrectomy is associated with slightly increase in the rates of post-operative complications such as perioperative bleeding and urinary fistulas which might lead to life-threatening conditions. This case shows surgery, which was performed for 39 year-old male patient with intraparenchymal kidney cancer and the postoperative course, complicated with rare vascular abnormality - renal artery-renal pelvis fistula. It demonstrates multidisciplinary oncourosurgical and endovascular approach of treating kidney cancer lesions that may provide successful organ-preserving results. The possibility of such complication in centrally localized tumors should be taken into account.